Technique of inter-computation for reactive electric power between small hydroelectric power stations and subjects of the wholesale market of the electric power of Ukraine - Rohalskyi, B. S.; Nanaka, O. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The analysis of existing "Techniques of payment for overflows of reactive electric power between power supply utilities and the consumers" is carried out. The technique of inter-computation for the reactive electric power between small hydroelectric power stations and subjects of the wholesale market of the electric power of Ukraine is offered.